2002
DOI: 10.1099/00221287-148-12-3801
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of yodA encoding a novel cadmium-induced protein in Escherichia coli The GenBank accession number for the E. coli yodA gene and the SWISS-PROT accession number for E. coli YodA protein in this paper are AAC75039 and P76344, respectively.

Abstract: Bacterial accommodation to moderate concentrations of cadmium is accompanied by transient activation of general stress proteins as well as a sustained induction of other proteins of hitherto unknown functions. One of the latter proteins was previously identified as the product of the Escherichia coli yodA ORF. The yodA ORF encodes 216 aa residues (the YodA protein) and the increased synthesis of YodA during cadmium stress was found probably to be a result of transcriptional activation from one single promoter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 46 publications
1
23
0
Order By: Relevance
“…These findings show that znuCB expression is enhanced by SoxS. In this regard, SoxS has been shown to affect the expression of other zinc transport factors during cobalt stress (40). Our findings also agree with a study that showed increased expression of members of the soxS regulon in response to low extracellular Zn 2ϩ concentrations in vitro (48).…”
Section: Discussionsupporting
confidence: 82%
“…These findings show that znuCB expression is enhanced by SoxS. In this regard, SoxS has been shown to affect the expression of other zinc transport factors during cobalt stress (40). Our findings also agree with a study that showed increased expression of members of the soxS regulon in response to low extracellular Zn 2ϩ concentrations in vitro (48).…”
Section: Discussionsupporting
confidence: 82%
“…The Z3065 protein is 99% identical to YodA from E. coli K-12, and the Z3065 gene and yodA are flanked by the same genes in their respective genomes. In E. coli K-12, YodA (recently renamed ZinT [24]) is a metal-binding protein that is secreted into the periplasm under stress conditions (6,40).…”
Section: Resultsmentioning
confidence: 99%
“…YodA was originally identified as a (40). The YodA crystal structure revealed that this protein binds to metal ions, including cadmium and zinc, and is structurally related to the lipocalin family of proteins (7).…”
Section: Discussionmentioning
confidence: 99%
“…The response of microorganisms to heavy metals, such as mercury and cadmium, has been studied in some detail (1,(7)(8)(9)(10)(11)(12). The toxic elements are primarily removed by active transport, reducing their intracellular concentration to acceptable levels (13).…”
mentioning
confidence: 99%